CD4+T Helper Cells and Regulatory T Cells in Active Lupus Nephritis - an Imbalance Towards a Predominant Th1 Response? - Mesquita Junior, Danilo [UNIFESP] (2016)
Univ Fed Sao Paulo, Internal Med, Sao Paulo, Brazil